TEMPERATURE DEPENDENCE OF THE EFFECTIVE DIFFUSION COEFFICIENTS OF COMBUSTION PRODUCTS OF METHANE, PROPANE AND BUTANE IN AIR - Zhavrin, Yu.I.; Kosov, V.N.; Poyarkov, I.V.; Fedorenko, O.V.; Asembaeva, M.K. (Recent Contributions to Physics, 2017)
Temperature dependence of the effective diffusion coefficients (EDC) and the matrix coefficients of multicomponent diffusion (MCMD) of products under full combustion of methane (0,0950СО2 + 0,1901Н2О + 0,7149N2), propane (0,1036СО2 + 0,1382Н2О + 0,7582N2) and butane (0,1043СО2 + 0,1304Н2О + 0,7653N2) in the air and its subsequent diffusion in the air in the temperature range from 298 to 1000 K and a pressure 0,101 MPa is calculated. Calculations were carried out for two flask diffusion apparatus. It is shown that the EDC and the diagonal MCMD for each component in the mixtures have its constant factor of the temperature dependence. For the nondiagonal coefficients MCMD the factor of the temperature dependence is not constant.